2015
DOI: 10.1080/00028487.2015.1057346
|View full text |Cite
|
Sign up to set email alerts
|

Consequences of Emergence Timing for the Growth and Relative Survival of Steelhead Fry from Naturally Spawning Wild and Hatchery Parents

Abstract: For many fishes, reproducing early in the year may present tradeoffs for the offspring: the drawbacks associated with harsh environmental conditions may be offset by advantages in competition for food and space. We investigated this tradeoff in a system where hatchery-origin steelhead Oncorhynchus mykiss were bred to spawn about 4 months earlier than wild-origin fish. Hatchery-origin adults were released into the wild and spawned in common with wild steelhead. Naturally spawned offspring from these matings wer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 66 publications
0
7
0
Order By: Relevance
“…The timing of adult migration is a heritable trait in salmonids, and has substantial fitness consequences if not synchronized with local environmental conditions (Flagg, Waknitz, Maynard, Milner, & Mahnken, ; Hess, Zendt, Matala, & Narum, ; Jones et al, ; McLean, Bentzen, & Quinn, ; Quinn, Peterson, Gallucci, Hershberger, & Brannon, ). Few natural‐origin summer steelhead were detected in the population, and lower numbers of putative hybrids were backcrossed to the hatchery summer steelhead, despite high abundances of hatchery summer steelhead in the population during reproduction.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The timing of adult migration is a heritable trait in salmonids, and has substantial fitness consequences if not synchronized with local environmental conditions (Flagg, Waknitz, Maynard, Milner, & Mahnken, ; Hess, Zendt, Matala, & Narum, ; Jones et al, ; McLean, Bentzen, & Quinn, ; Quinn, Peterson, Gallucci, Hershberger, & Brannon, ). Few natural‐origin summer steelhead were detected in the population, and lower numbers of putative hybrids were backcrossed to the hatchery summer steelhead, despite high abundances of hatchery summer steelhead in the population during reproduction.…”
Section: Discussionmentioning
confidence: 99%
“…Few natural‐origin summer steelhead were detected in the population, and lower numbers of putative hybrids were backcrossed to the hatchery summer steelhead, despite high abundances of hatchery summer steelhead in the population during reproduction. Jones et al () found similar proportions of hatchery, hybrid, and wild steelhead in a stream in south‐west Washington (1% natural‐origin, hatchery‐lineage steelhead and 29% hybrids), and concluded that the earlier‐spawning hatchery steelhead were emerging during unfavourable conditions; however, the later‐emerging hatchery steelhead were more likely to encounter better environmental conditions for early rearing, resulting in selection for this later migration timing that is more similar to the native population.…”
Section: Discussionmentioning
confidence: 99%
“…Genomic DNA was isolated using a NucleoSpin ® (Macherey-Nagel) kit following the manufacturer's instructions. We amplified 96 SNPs (Table S1) that yielded polymorphic multilocus genotypes in both native (Jones et al, 2015) and naturalized rainbow trout populations (Benavente et al, 2015) (Table S2). Multiplex PCR was carried out using Fluidigm ® 96.96 dynamic array chips following Seeb, Pascal, Ramakrishnan, and Seeb (2009) and procedures of Smith et al (2011) for a pre-amplification step to increase PCR copies under low template DNA concentration.…”
Section: Molecular Procedures Exploratory Analyses and Snp Selectionmentioning
confidence: 99%
“…Substantial releases of hatchery-origin salmonids influence natural populations through ecological mechanisms in both freshwater and marine environments (Naish et al 2008, Rand et al 2012. Interbreeding with hatchery stocks can shift natural population trait distribution by producing offspring with traits intermediate between parental populations (Seamons et al 2012, Jones et al 2015, potentially resulting in reduced survival (Araki et al 2009). Over several generations, phenotypic traits of a natural population can be largely replaced by those of a hatchery population (Ford et al 2006).…”
Section: Introductionmentioning
confidence: 99%